Lakon Banjaran : Apa dan Bagaimana ? - Timbul Subagya (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2007)
As we know that before Ki Nartasabda appears, puppet society only has standard story (lakon baku) or jejer, carangan and/or carang kadhapur. The appearance of banjaran puppet in 1970s by Ki Nartasabda leads to the pros and cons in puppet society. Nevertheless, the kind of story is often presented by some dalag today. This paper illuminates briefly about the existence of banjaran puppet story introduced by Ki Nartasabda. Because of the minimum abservation, this paper just tries to convey what andÂ  how the storyÂ  of banjaran is and is still seem incomplete.Key words: lakon banjaran, Nartasabda.